ECUME COMMUNITY WEBSITE MAKING USING JOOMLA STMIK JAKARTA AND APPSERV. - Ridwan Oliver Pangihutan; Melani Dewi Lusita, Skom, MMSI (Jurnal Sistem Informasi, 2010)
Media information is a means to convey a message or information can we receive,both orally and in writing, and various kinds such as newspapers, television, radioand komputer.Internet is one medium of information very quickly. The requiredinformation must be information very quickly, accurately, and can be heldresponsible for authenticity. Ecumenical Fellowship (PO) is one of the centralinformation and aspirations of students of Christian STMIK STI & K. JakartaHopefully with the PO website is expected to facilitate student / i STMIK Christianspirituality Jakarta to obtain information as desired.